Los pictogramas y el lenguaje oral en los niños del nivel inicial II de la Escuela de Educación Básica Cuidad de Loja, periodo académico 2021-2022. - Medina Quichimbo, Daniela Michelle (2022)
Oral language is a vital system of expression of the human being since it helps to make ideas, thoughts, desires or opinions known, through the use of sounds articulated by the voice. The objective of this study was to determine how pictograms strengthen oral language in children of initial level II of the Ciudad de Loja School of Basic Education, period 2021-2022. The research was framed in a mixed approach that allowed analyzing and collecting qualitative and quantitative information; the scope was descriptive, since it facilitated obtaining information on the variables and describing the phenomenon that caused the children's speech delay; Analytical-synthetic methods were used that served to collect information and perform the analysis of the variables investigated and the inductive-deductive method that helped give meaning and order to the present work to formulate the proposed objectives and establish the conclusions and recommendations. The PLON-R Test was used as an instrument, through which it was shown that 52% of the children were at a level of language delay, presenting difficulties in the pronunciation and articulation of phonemes such as s, p, v, d , t, r, ll, l, m, t. To reduce these difficulties, a guide based on pictograms was designed and applied. After the activities and the application of the post test, it was observed that 70% of the children improved their oral language. Concluding that the pictograms were very useful in the development of this area, however, it was not possible to achieve 100% effectiveness, due to the short time for the execution of the activities. Keywords: Linguistics, Phonetics, Communication, Reading, Pictorial, Expression.